Obesity and Preeclampsia: Common Pathophysiological Mechanisms - Lopez-Jaramillo, Patricio; Barajas, Juan; Rueda-Quijano, Sandra M.; Lopez-Lopez, Cristina; Felix, Camilo (Frontiers in Physiology, 2018)
Preeclampsia is a disorder specific of the human being that appears after 20 weeks of pregnancy, characterized by new onset of hypertension and proteinuria. Abnormal placentation and reduced placental perfusion associated to impaired trophoblast invasion and alteration in the compliance of uterine spiral arteries are the early pathological findings that are present before the clinical manifestations of preeclampsia. Later on, the endothelial and vascular dysfunction responsible of the characteristic vasoconstriction of preeclampsia appear. Different nutritional risk factors such as a maternal deficit in the intake of calcium, protein, vitamins and essential fatty acids, have been shown to play a role in the genesis of preeclampsia, but also an excess of weight gain during pregnancy or a pre-pregnancy state of obesity and overweight, which are associated to hyperinsulinism, insulin resistance and maternal systemic inflammation, are proposed as one of the mechanism that conduce to endothelial dysfunction, hypertension, proteinuria, thrombotic responses, multi-organ damage, and high maternal mortality and morbidity. Moreover, it has been demonstrated that pregnant women that suffer preeclampsia will have an increased risk of future cardiovascular disease and related mortality in their later life. In this article we will discuss the results of studies performed in different populations that have shown an interrelationship between obesity and overweight with the presence of preeclampsia. Moreover, we will review some of the common mechanisms that explain this interrelationship, particularly the alterations in the L-arginine/nitric oxide pathway as a crucial mechanism that is common to obesity, preeclampsia and cardiovascular diseases.